2018
DOI: 10.1002/jez.2164
|View full text |Cite
|
Sign up to set email alerts
|

Dim artificial light at night affects mating, reproductive output, and reactive oxygen species in Drosophila melanogaster

Abstract: Humans are lighting the night-time environment with ever increasing extent and intensity, resulting in a variety of negative ecological effects in individuals and populations. Effects of light at night on reproductive fitness traits are demonstrated across taxa however, the mechanisms underlying these effects are largely untested. One possible mechanism is that light at night may result in perturbed reactive oxygen species (ROS) and oxidative stress levels. Here, we reared Drosophila melanogaster under either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 61 publications
(86 reference statements)
1
30
0
1
Order By: Relevance
“…A major aim of our special issue was to reveal the multitude of molecular, physiological, and behavioral mechanisms that light pollution can affect. At the molecular and physiological level, these and previous papers have shown that ALAN can alter patterns of gene expression (Bedrosian, Galan, Vaughn, Weil, & Nelson, 2013;Dominoni et al, 2018;Fonken & Nelson, 2014;Shuboni & Yan, 2010), hormone secretion (Alaasam et al, 2018;de Jong et al, 2016;Dominoni, Goymann, Helm, & Partecke, 2013;Ouyang, Davies, & Dominoni, 2018), body temperature (Kumar et al, 2018), energy expenditure (Welbers et al, 2017), immune function (Bedrosian, Fonken, Walton, & Nelson, 2011;Cissé, Russart, & Nelson, 2017;Fonken, Lieberman, Weil, & Nelson, 2013), and oxidative stress (McLay et al, 2018;Navara & Nelson, 2007). Given, such extensive changes in the underlying physiology, it comes with no surprise that an impressive array of behavioral effects of ALAN have been shown.…”
Section: The Effects Of Alan At Different Levels Of Biological Orgamentioning
confidence: 88%
See 2 more Smart Citations
“…A major aim of our special issue was to reveal the multitude of molecular, physiological, and behavioral mechanisms that light pollution can affect. At the molecular and physiological level, these and previous papers have shown that ALAN can alter patterns of gene expression (Bedrosian, Galan, Vaughn, Weil, & Nelson, 2013;Dominoni et al, 2018;Fonken & Nelson, 2014;Shuboni & Yan, 2010), hormone secretion (Alaasam et al, 2018;de Jong et al, 2016;Dominoni, Goymann, Helm, & Partecke, 2013;Ouyang, Davies, & Dominoni, 2018), body temperature (Kumar et al, 2018), energy expenditure (Welbers et al, 2017), immune function (Bedrosian, Fonken, Walton, & Nelson, 2011;Cissé, Russart, & Nelson, 2017;Fonken, Lieberman, Weil, & Nelson, 2013), and oxidative stress (McLay et al, 2018;Navara & Nelson, 2007). Given, such extensive changes in the underlying physiology, it comes with no surprise that an impressive array of behavioral effects of ALAN have been shown.…”
Section: The Effects Of Alan At Different Levels Of Biological Orgamentioning
confidence: 88%
“…From insects to mammals, several animal classes, both invertebrate and vertebrate, are represented. McLay, Nagarajan-Radha, Green, and Jones (2018) investigated effects of ALAN on reproduction and physiology in Drosophila. Insects were also the focus of Donners et al (2018), who modeled the attraction of several insect orders to light sources of different colors, allowing the application of light sources that reduce insect attraction.…”
Section: The Effects Of Alan On Different Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the pink bollworm Pectinophora gossypiella can be artificially entrained by monochromatic yellow light emitted by low‐pressure sodium (LPS) lamps (Pittendrigh & Minis, ), and diurnal Bombus terrestris bumblebees by UV illumination (Chittka , Stelzer, & Stanewsky, ). Desynchronization reduces reproductive fitness of Drosophila melanogaster fruit flies (Xu, DiAngelo, Hughes, Hogenesch, & Sehgal, , see also McLay, Nagarajan‐Radha, Green, & Jones, ) and has the potential to disrupt vital biological processes in other taxa (Dominoni, Borniger, & Nelson, ; Gaston et al, ; Saunders, ).…”
Section: Temporal Disorientationmentioning
confidence: 99%
“…Apart from acting as an ecological trap (Eisenbeis, ; Frank, ; Macgregor et al, ), light pollution harms insects by impeding communication, changing their physiology, life‐history traits and night habits, for example, migration, feeding and reproductive behaviour. ALAN was found to inhibit initiation of pupal diapause (van Geffen et al, ), reduce sex pheromone production (van Geffen et al, ), reduce mating (van Geffen et al, ) and interrupt feeding in moths (van Langevelde et al, ), reduce courtship behaviour and mating success in fireflies (Firebaugh & Haynes, ), decrease fecundity and adult survival, prolong courtship and alter oviposition patterns in Drosophila melanogaster (McLay et al, , ). By decreasing fitness, survival and reproduction, ALAN can increase mortality and decrease reproduction rates and population growth.…”
Section: Evidence For Disruptive Impacts Of Artificial Light At Nightmentioning
confidence: 99%